2019
DOI: 10.1038/s41598-019-55985-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation and oxidation in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common and lethal primary malignant brain tumor in adults. Despite the multimodal standard treatments for GBM, the median survival is still about one year. Analysis of brain tissues from GBM patients shows that lipid droplets are highly enriched in tumor tissues while undetectable in normal brain tissues, yet the identity and functions of lipid species in GBM are not well understood. The aims of the present work are to determine how GBM utilizes fatty acids, and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 45 publications
4
82
0
Order By: Relevance
“…But inhibition of LDs rescued PA-induced lipotoxicity, the reason for which is unclear. It has been reported that PA or EPA treatment-induced apoptosis while OA treatment increased the proliferation rate of glioma cells 23 , 36 , 37 , which are consistent with our results. And the inhibition of DGAT1 in PA-treated cells would increase C16 ceramide which induced tumor growth while C18 ceramide did not 11 , 55 , inferring that inhibition of PA-induced LDs may lead to a worse outcome in treating gliomas.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…But inhibition of LDs rescued PA-induced lipotoxicity, the reason for which is unclear. It has been reported that PA or EPA treatment-induced apoptosis while OA treatment increased the proliferation rate of glioma cells 23 , 36 , 37 , which are consistent with our results. And the inhibition of DGAT1 in PA-treated cells would increase C16 ceramide which induced tumor growth while C18 ceramide did not 11 , 55 , inferring that inhibition of PA-induced LDs may lead to a worse outcome in treating gliomas.…”
Section: Discussionsupporting
confidence: 93%
“…We observed and quantified LDs formation and changes of unsaturation level of LD lipids with label-free SRS imaging. We found that PA or EPA treatment reduced glioma cell viability, but OA treatment enhanced cell viability and proliferation, which were consistent with the previous studies 23 , 36 , 37 . By inhibiting the final step of the biosynthesis of TAG (i.e., inhibiting DGAT1 and DGAT2) for LDs formation 38 – 41 , the LDs were significantly reduced with all three FAs treatments.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lipid metabolism is abnormally regulated in gliomas compared to normal cells, with changes in the expression of lipid-related genes such as SREBP1 and FAS, which results in altered lipid composition and lipogenesis to keep up with energy demands. 10,14,15 Lipid droplets are cytosolic organelles that, among other functions, serve as a storage medium for the fatty acids used as an energy source to maintain rapid proliferation in unfavorable microenvironments. Lipid droplet formation particularly occurs under stressful conditions such as hypoxia and nutrient deprivation.…”
Section: Introductionmentioning
confidence: 99%